The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s2236-89062010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura espacial e diamétrica de espécies arbóreas e seus condicionantes em um fragmento de cerrado sentido restrito no sudoeste goiano

Abstract: -(Spatial distribution pattern and size structure of tree species and its structuring factors in a fragment of the Brazilian cerrado). The aim of this study was to analyze population structure and spatial distribution pattern of five tree species in a fragment of cerrado stricto sensu in the southwest of the Goiás State, Brazil. Fifty quadrats of 10 × 10 m (100 m 2 ) were surveyed, and all individuals within each quadrat were sampled. The theoric distributions of Poisson and Negative Binomial and two indices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
0
10
0
7
Order By: Relevance
“…The vegetation dynamics showed that the number of recruits was higher than number of dead trees in all periods and areas measured. This result points out to the self-regeneration behavior of the vegetation (Bernasol & Lima-Ribeiro, 2010;Mews et al, 2011;Carvalho, Fagg, & Felfili, 2010). Accordingly, the recruitment rate stood out in relation to mortality rate in all areas, in the respective time intervals.…”
Section: Resultsmentioning
confidence: 64%
“…The vegetation dynamics showed that the number of recruits was higher than number of dead trees in all periods and areas measured. This result points out to the self-regeneration behavior of the vegetation (Bernasol & Lima-Ribeiro, 2010;Mews et al, 2011;Carvalho, Fagg, & Felfili, 2010). Accordingly, the recruitment rate stood out in relation to mortality rate in all areas, in the respective time intervals.…”
Section: Resultsmentioning
confidence: 64%
“…O padrão de distribuição espacial agregada é comum entre outras espécies arbóreas (SOUZA; COIMBRA, 2005; ALMEIDA; CORTINES, 2008;BENASOL;LIMA-RIBEIRO, 2010;BRUZINGA et al, 2013). Dessa forma, os processos que atuam de forma negativa sobre a espécie estudada também podem ter efeitos pungentes sobre outras espécies com distribuição parecida.…”
Section: Varella T L Et Al 122unclassified
“…The studied populations did not present a diametrical distribution in the form of "inverted J", that is, in which the number of individuals is reduced from the smallest diameter classes to the largest. The distribution of individuals in the form of "inverted J" is reported by several authors as an indicator of population stability and ability to self-regenerate and reproduce under closed canopy (Gonçalves & Santos, 2008;Bernasol & Lima-Ribeiro, 2010;Figueiredo Filho et al, 2010;Abreu et al, 2014;Silva et al, 2015). In areas 2, 3 and 4, the distribution was characterized as "bell-shaped" (Bernasol & Lima-Ribeiro, 2010), that is, with most individuals in the intermediate classes.…”
Section: /9mentioning
confidence: 99%